PENGARUH KEPUASAN KERJA, STRES KERJA, DAN LINGKUNGAN KERJA TERHADAP TURNOVER INTENTION PADA KARYAWAN GENERASI Z (STUDI PADA KARYAWAN TETAP PT.XYZ) - Ramadhani, Mutiara Ayu Alzahra; Wardani, Deni (Journal of Accounting, Management and Islamic Economics, 2025)
This research aims to examine "The Influence of Job Satisfaction, Job Stress, and Work Environment on Turnover Intention in Generation Z Employees (Study of Generation Z Employees, PT XYZ)". The independent variables in this research are Job Satisfaction, Job Stress, and Work Environment. Meanwhile, the dependent variable in this research is Turnover Intention. Hypothesis testing in this research uses the PLS or Partial Least Square method with SmartPLS 4.0 software. The data collection technique uses a Google Form application questionnaire to collect respondent information. The sample in this study was Generation Z Employees at PT XYZ. Gen Z employees from 1997-2012 in the 2023 period and 46 Respondent Gen Z Employees at PT XYZ. The results of the analysis show that the Work Environment has no effect on Turnover Intention, Job Satisfaction has a negative effect on Turnover Intention, and Job Stress has a positive effect on Turnover Intention.